1989
DOI: 10.1111/j.1365-2133.1989.tb01357.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-symmetric subcutaneous lipomatosis associated with familial combined hyperlipidaemia

Abstract: A family with familial combined hyperlipidaemia in which affected members had nonsymmetric subcutaneous lipomatosis (NSSCL) is described. Affected members had high serum levels of total cholesterol, low density lipoprotein (LDL) cholesterol and high density lipoprotein (HDL) cholesterol. By contrast, family members without NSSCL had normal lipid levels. There was also a correlation between the degree of hyperlipidaemia and the amount of subcutaneous lipomas. The occurrence of hyperlipidaemia in family members … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 6 publications
1
15
0
1
Order By: Relevance
“…FML aetiology is still unknown. Occasional coexistence of FML with hyperlipidemia has been reported [5]; our patient had repeatedly normal lipid profile despite his marked obesity of genetic predisposition. No hypothesis on the immunologic basis of this disorder or any association with autoimmune conditions has been reported to date.…”
Section: Discussionmentioning
confidence: 86%
“…FML aetiology is still unknown. Occasional coexistence of FML with hyperlipidemia has been reported [5]; our patient had repeatedly normal lipid profile despite his marked obesity of genetic predisposition. No hypothesis on the immunologic basis of this disorder or any association with autoimmune conditions has been reported to date.…”
Section: Discussionmentioning
confidence: 86%
“…It is a matter of debate whether familial multiple lipomatosis is associated with abnormalities of lipid metabolism. Some of the authors like Wilson and Rubinstein mentioned that familial multiple lipomatosis might be associated with hyperlipidemia [2,3]. However, the patient presented above had hypertriglyceridemia and low HDL cholesterol levels.…”
Section: Discussionmentioning
confidence: 90%
“…1,14 Factors such as overweight and exacerbated growth of nodules during and after pregnancies suggest that exogenous factors (diet), metabolic changes (dyslipidemia or alterations in fatty acid desaturation) and hormonal mechanisms may be involved in adipocyte hyperplasia. 32 differences in enzymatic desaturation of stearoyl-CoA between individuals with rare adipose disorders (RAD) and obese control group and concluded that individuals with FML and obesity showed the highest rates of desaturation, thus increasing the lipogenesis process. 32,34 One unexpected finding was that patient A was the only within the casuistic and her family group to manifest pain, daily weakness, fatigue, and psychiatric comorbidity (chronic depression and anxiety disorder).…”
Section: Discussionmentioning
confidence: 99%